Meningkatkan Kemampuan Literasi Siswa melalui Gerakan Literasi Sekolah - Dodo, Dodo (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
In today's rapidly evolving world, literacy has become an essential skill for individuals to navigate and succeed in various aspects of life. Literacy is not limited to reading and writing but also encompasses critical thinking, comprehension, and communication skills. Recognizing the significance of literacy, many educational institutions and organizations have initiated programs and movements to enhance the literacy capabilities of students. One such movement is the School Literacy Movement. This study aims to explore gerakan literasi sekolah and its impact on the growth of students' literacy skills.